The Seductive Power of an Innovation: Enrolling Non-conventional Actors in a Drip Irrigation Community in Morocco. Issue 1 (1st January 2016) - Benouniche, Maya; Errahj, Mostafa; Kuper, Marcel
Abstract: Purpose: The aim of this study was to analyze the motivations of non-conventional innovation actors to engage in innovation processes, how their involvement changed the technology and their own social-professional status, and to analyze their role in the diffusion of the innovation. Design/methodology/approach: We studied the innovation process of drip irrigation in Morocco. We interviewed 35 farmers in two villages, selected to represent a diversity of farms, and observed their drip irrigation systems. We interviewed several local artisans and traders, and intermediaries about their social-professional pathway, using a checklist to understand their motivations and their involvement with drip irrigation. Findings: We showed how a variety of non-conventional actors became involved in drip irrigation, leading to the progressive creation of an active inter-related socio-technical network involved in the sales, manufacturing, fitting, and use of drip irrigation systems. This network challenged an imported technology promoted by irrigation companies that targeted large-scale farmers, and transformed it into drip irrigation systems adapted to a wide range of situations and farmers, including small-scale farmers. The involvement of these actors led to reciprocal changes in the technology and in the socio-professional status of the intermediaries, hence accelerating the diffusion of the innovation. Practical implications: Understanding the motivations of non-conventional innovation actors helps comprehend the multiple pathways of innovation processes, and the socio-professional pathways of innovation actors. It is worth considering integrating these actors in state programs and other planned innovation processes, as they are near to field realities and to innovation users, and are able to adapt a technology to local requirements. Originality/value: The results of this study contribute to the scientific debate about the mutually beneficial alliance of non-conventional actors and technical innovations.